Applicability of prewhitening to eliminate the influence of serial correlation on the Mann‐Kendall test - Yue, Sheng; Wang, Chun Yuan (Water Resources Research, 2002)
Prewhitening has been used to eliminate the influence of serial correlation on the Mann‐Kendall (MK) test in trend‐detection studies of hydrological time series. However, its ability to accomplish such a task has not been well documented. This study investigates this issue by Monte Carlo simulation. Simulated time series consist of a linear trend and a lag 1 autoregressive (AR(1)) process with a noise. Simulation results demonstrate that when trend exists in a time series, the effect of positive/negative serial correlation on the MK test is dependent upon sample size, magnitude of serial correlation, and magnitude of trend. When sample size and magnitude of trend are large enough, serial correlation no longer significantly affects the MK test statistics. Removal of positive AR(1) from time series by prewhitening will remove a portion of trend and hence reduces the possibility of rejecting the null hypothesis while it might be false. Contrarily, removal of negative AR(1) by prewhitening will inflate trend and leads to an increase in the possibility of rejecting the null hypothesis while it might be true. Therefore, prewhitening is not suitable for eliminating the effect of serial correlation on the MK test when trend exists within a time series.
Keywords: Ouvrage_Collectif_Numéro1

Riverine landscape diversity - Ward, J. V.; Tockner, K.; Arscott, D. B.; Claret, C. (Freshwater Biology, 2002)
1. This review is presented as a broad synthesis of riverine landscape diversity, beginning with an account of the variety of landscape elements contained within river corridors. Landscape dynamics within river corridors are then examined in the context of landscape evolution, ecological succession and turnover rates of landscape elements. This is followed by an overview of the role of connectivity and ends with a riverine landscape perspective of biodiversity. 2. River corridors in the natural state are characterised by a diverse array of landscape elements, including surface waters (a gradient of lotic and lentic waterbodies), the fluvial stygoscape (alluvial aquifers), riparian systems (alluvial forests, marshes, meadows) and geomorphic features (bars and islands, ridges and swales, levees and terraces, fans and deltas, fringing floodplains, wood debris deposits and channel networks). 3. Fluvial action (erosion, transport, deposition) is the predominant agent of landscape evolution and also constitutes the natural disturbance regime primarily responsible for sustaining a high level of landscape diversity in river corridors. Although individual landscape features may exhibit high turnover, largely as a function of the interactions between fluvial dynamics and successional phenomena, their relative abundance in the river corridor tends to remain constant over ecological time. 4. Hydrological connectivity, the exchange of matter, energy and biota via the aqueous medium, plays a major though poorly understood role in sustaining riverine landscape diversity. Rigorous investigations of connectivity in diverse river systems should provide considerable insight into landscape‐level functional processes. 5. The species pool in riverine landscapes is derived from terrestrial and aquatic communities inhabiting diverse lotic, lentic, riparian and groundwater habitats arrayed across spatio‐temporal gradients. Natural disturbance regimes are responsible for both expanding the resource gradient in riverine landscapes as well as for constraining competitive exclusion. 6. Riverine landscapes provide an ideal setting for investigating how complex interactions between disturbance and productivity structure species diversity patterns.
Keywords: Ouvrage_Collectif_Numéro1

Climatic control of river‐ice hydrology: a review - Prowse, Terry D.; Beltaos, Spyros (Hydrological Processes, 2002)
Abstract Ice is present during a part of the year on many rivers of cold, and even temperate, regions of the globe. Though largely ignored in hydrological literature, river ice has serious hydrologic impacts, including extreme flood events caused by ice jams, interference with transportation and energy production, low winter flows and associated ecological and water quality consequences. It is also a major factor in the life cycle of many aquatic and other species, being both beneficial and destructive, depending on location and time of year. A brief review of the hydrologic aspects of river ice shows strong climatic links and illustrates the sensitivity of the entire ice regime to changes in climatic conditions. To date, this sensitivity has only partly been documented: the vast majority of related studies have focused on the timing of freeze‐up and break‐up over the past century, and indicate trends that are consistent with concomitant changes in air temperature. It is only in the past few years that attention has been paid to the more complex, and practically more important, question of what climatic change may do to the frequency and severity of extreme ice jams, floods and low flows. The probable changes to the ice regime of rivers, and associated hydrological processes and impacts, are discussed in the light of current understanding. Copyright © 2002 John Wiley & Sons, Ltd.
Keywords: Ouvrage_Collectif_Numéro1

Climatic impacts on the runoff generation processes in British Columbia, Canada - Loukas, A.; Vasiliades, L.; Dalezios, N.R. (Hydrology and Earth System Sciences, 2002)
Abstract. The potential impact of future climate change on runoff generation processes in two southern British Columbia catchments was explored using the Canadian Centre for Climate Modelling Analysis General Circulation Model (CGCMa1) to estimate future changes in precipitation, temperature and cloud cover while the U.B.C. Watershed Model was used to simulate discharges and quantify the separate runoff components, i.e. rainfall, snowmelt, glacier melt and groundwater. Changes, not only in precipitation and temperature but also in the spatial distribution of precipitation with elevation, cloud cover, glacier extension, altitude distribution of vegetation, vegetation biomass production and plant physiology were considered. The future climate of the catchments would be wetter and warmer than the present. In the maritime rain-fed catchment of the Upper Campbell, runoff from rainfall is the most significant source of flow for present and future climatic conditions in the autumn and winter whereas runoff from groundwater generates the flow in spring and summer, especially for the future climate scenario. The total runoff, under the future climatic conditions, would increase in the autumn and winter and decrease in spring and summer. In contrast, in the interior snow-covered Illecillewaet catchment, groundwater is the most significant runoff generation mechanism in the autumn and winter although, at present, significant flow is generated from snowmelt in spring and from glacier runoff in summer. In the future scenario, the contribution to flow from snowmelt would increase in winter and diminish in spring while the runoff from the glacier would remain unchanged; groundwater would then become the most significant source of runoff, which would peak earlier in the season. Keywords: climatic change, hydrological simulation, rainfall, snowmelt, runoff processes
Keywords: Ouvrage_Collectif_Numéro1